The Effect of Ethanol Extract of Senggani Leaves (Melastoma malabathricum) on Reducing Paw Edema in Rats Induced By Carrageenan - Enis, Rina Nofri; Ekaputri, Tia Wida; Dewi, Hasna; Wulandari, Putri Sari (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2025)
Background: The extract of senggani leaves (Melastoma malabathricum) has attracted attention as a potential anti-inflammatory agent due to its diverse phytochemical content, including flavonoids, tannins, and other polyphenols, which have been shown to possess antioxidant and anti-inflammatory activities in several previous studies. This study aims to determine the difference in the percentage of inflammation inhibition of paw edema in rats induced by carrageenan through the administration of senggani leaves extract. Methods: In this study, 24 rats were divided into 4 groups. Negative control group was given Na-CMC 0.5%, Positive control group was given Na-diclofenac 50 mg/kg BW. Two dosage groups were given senggani extract solution at 250 and 500 mg/kg BW. Carrageenan is used to induce local inflammation by injecting a 2% carrageenan solution in physiological NaCl subcutaneously into the subplantar region of all test animal groups to elicit an edema response. Paw thickness is measured using calipers at hour 0 before inflammation induction, followed by measurements at hours 1, 2, 3, 4, and 5. Results: The peak inhibitory effect (62.10% and 60.41%) for both doses of senggani extract was observed at the 3rd hour, suggesting a rapid onset of action. At the higher dose (500 mg/kg BW), senggani extract exhibited comparable or even slightly superior inhibitory effects to Na-diclofenac. Conclusion: Senggani extract has potential as a natural anti-edema agent. Further research is needed to explore its mechanism of action and optimize its therapeutic use.